Kajian Literatur tentang Investasi Alternatif untuk Meningkatkan Efektivitas Diversifikasi di Era Modern - Dian Mutiara Simamora; Muhammad Ariansyah; Tiara Ananta Sinaga; Nurhalizah Pasha; Adelia Rizky Matondang (Polyscopia, 2026)
This study examines the role of alternative investments in enhancing portfolio diversification effectiveness in the modern era, characterized by rapid economic dynamics, financial technology innovation, and growing investor demand for adaptive investment instruments. The research addresses the question of how alternative assets contribute to risk mitigation and portfolio stability compared to traditional investments. Employing a qualitative literature review method, this study synthesizes findings from recent empirical and theoretical studies on alternative investments, including cryptocurrencies, digital gold, fintech lending, alternative mutual funds, and collectible assets. The findings indicate that alternative investment instruments offer significant diversification benefits due to their relatively low correlation with conventional financial markets, thereby reducing concentrated risk and improving portfolio resilience. Furthermore, advancements in financial technology have expanded accessibility and participation across diverse investor segments, reinforcing the strategic relevance of alternative assets. This study argues that alternative investments constitute a viable long-term diversification strategy for modern investors navigating global economic uncertainty and seeking more robust, resilient portfolio structures.